Perlindungan Terhadap Korban Sekaligus Pelaku Pada Tindak Pidana Penyalahgunaan Narkotika Berdasarkan Putusan Nomor. 104/Pid.B/2014/PN.BJ - Weni Safitri Ismail; Erdianto Effendi; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The criminal misuse of narcotic basically only considered a suspect of an act that iswhere the real perpetrators are also victims of drug abuse of narcotic crime itself. As is thecase based on the decision of the District Court Binjai No.104 / Pid.B / 2014 / PN.BJ. Againstthe defendant shall be punished with imprisonment of 1 (one) year and set a period ofdetention already served by the accused entirely deducted from the sentence imposed.Whereas in Act 35 of 2009 Article 54 has been explained that addicts and drug abusers shallbe rehabilitated. The purpose of this thesis are: First, to determine the urgency of theprotection of victims and perpetrators in the crime of drug abuse. Secondly, To find out theverdict in the case No. 104 / Pid.B / 2014 / PN.BJ has provided protection against the accusedwho is the perpetrator and victim.This type of research used by the author in this study is normative. Source of dataused are secondary data. Data collection techniques in this study using literature.From the research problem there are two main things that can be inferred. First, protectionagainst perpetrators who are also victims of drug abuse in a criminal act is necessary.Secondly, the Decision Case Number. 104 / Pid.B / 2014 / PN.BJ. This does not giveprotection to sipelaku drug users which in this case can also be mentioned as a victim of thecrime of narcotics. Suggestions author, First, the judge in this case represents the state toprotect society should provide decision useful for individuals themselves and for society bypromoting prinsi fairness and in accordance with regulations or laws applicable. Secondly, interms of decision Case Number. 104 / Pid.B / 2014 / PN.BJ not provide that protection basedbecause the judge simply looked at the accused as the perpetrator and does not pay attentionto aspects of the victimKeywords : Protection - Victims - Perpetrators - Abuse - Narcotics